Cloning is Reviewed From the Perspective of Islam and Health - Ismail, Diauddin; Agustina, Fitriani (International Journal of Engineering, Science and Information Technology, 2021)
Islam as religion that applies universally and etemally encourage its people to have a positive and constructive attitude towords the development of science and technology (Science and technology),as long as science and technology is in line with Islamic law. The issue of genetic engineering the most recent isuue of cloning has become a hot ethical polemic in the west. This paper explores the Islamic view around the issue of cloning. According to Islamic law, it tums out that is no clear information that regulates this isuue.Among the mujtahids there is no question cloning animals, but if this is applied to human it will cause problems. Because cloning without the need for male sperma/husband. Without going through marriage, marriage guardian issues and other. This discourse is still developimg, but to arrive at a fatwa that allows it is still waiting for the continuation of the human cloning process in the future.